Posttranslational regulation of Fas ligand function - Voss, Matthias (BioMed Central, 2008)
The TNF superfamily member Fas ligand acts as a prototypic death factor. Due to its ability to induce apoptosis in Fas (APO-1, CD95) expressing cells, Fas ligand participates in essential effector functions of the immune system. It is involved in natural killer cell- and T cell-mediated cytotoxicity, the establishment of immune privilege, and in termination of immune responses by induction of activation-induced cell death. In addition, Fas ligand-positive tumours may evade immune surveillance by killing Fas-positive tumour-infiltrating cells. Given these strong cytotoxic capabilities of Fas ligand, it is obvious that its function has to be strictly regulated to avoid uncontrolled damage. In hematopoietic cells, the death factor is stored in secretory lysosomes and is mobilised to the immunological synapse only upon activation. The selective sorting to and the release from this specific lysosomal compartment requires interactions of the Fas ligand cytosolic moiety, which mediates binding to various adapter proteins involved in trafficking and cytoskeletal reorganisation. In addition, Fas ligand surface expression is further regulated by posttranslational ectodomain shedding and subsequent regulated intramembrane proteolysis, releasing a soluble ectodomain cytokine into the extracellular space and an N-terminal fragment with a potential role in intracellular signalling processes. Moreover, other posttranslational modifications of the cytosolic domain, including phosphorylation and ubiquitylation, have been described to affect various aspects of Fas ligand biology. Since FasL is regarded as a potential target for immunotherapy, the further characterisation of its biological regulation and function will be of great importance for the development and evaluation of future therapeutic strategies.